2012
DOI: 10.1113/jphysiol.2011.225862
|View full text |Cite
|
Sign up to set email alerts
|

The role of the TRPV6 channel in cancer

Abstract: The TRPV6 channel belongs to the superfamily of transient receptor potential (TRP) channels, subfamily vanilloid, member 6. Its expression in health is mainly confined to epithelial tissue of different organs such as digestive tract, kidney, testis, ovaries and skin. Due to its high calcium selectivity over other TRP channels, this channel was shown to participate in close regulation of calcium homeostasis in the body. In cancer a number of pieces of evidence demonstrate its upregulation and correlation with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 50 publications
0
85
0
Order By: Relevance
“…We showed that TRPV6 expression may also occur in BHP at a relatively weak level, and its expression at the protein level increases significantly in ADCs having a Gleason score of 7 and 9. An exhaustive synopsis of TRPV6 occurrence in various human tumors and the techniques used to study its expression have recently been published (26).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that TRPV6 expression may also occur in BHP at a relatively weak level, and its expression at the protein level increases significantly in ADCs having a Gleason score of 7 and 9. An exhaustive synopsis of TRPV6 occurrence in various human tumors and the techniques used to study its expression have recently been published (26).…”
Section: Discussionmentioning
confidence: 99%
“…Schwarz et al (24) suggested that TRPV6 increases the rate of prostate cancer HEK-293 cell proliferation in a Ca 2+ -dependent manner and correlates with slightly increased [Ca 2+ ] I . Lehen'kyi et al (25) found that TRPV6 silencing in prostate cancer LNCaP cells decreased the cell proliferation rate and the percentage of cells in the S-phase of the cell cycle. Peters et al (6) also found a reduced percentage of estrogen receptor-negative breast cancer cells in the S-phase after TRPV6 small interfering RNA treatment.…”
Section: +mentioning
confidence: 99%
“…Consistent with this notion, it was shown that the proliferation-promoting action of a1-adrenoreceptor (a1-AR) agonists on prostate cancer (PCa) cells is based on preferred coupling of the a1-AR-coupled signalling pathway to activation of a member of transient receptor potential (TRP) channel family, TRPC6, Ca 2þ influx through which in turn specifically regulates NFAT in a Ca 2þ /calcineurin-dependent manner [17]. In addition, in LNCaP PCa cells yet another highly oncogenic TRP member, TRPV6 [18], was shown to support high proliferation rates apparently by providing constitutive Ca 2þ influx required for subsequent downstream NFAT activation [19]. TRPV6 expression in PCa cells is also positively regulated by vitamin D3 receptor (VDR) activation to enhance [Ca 2þ ] C and proliferation of cells [20].…”
Section: Ca 2þ Remodelling That Promotes Proliferationmentioning
confidence: 99%